Lateral mechanical impedance rather than frontal promotes cortical expansion of roots. (2nd June 2020) - Feng, Xuanjun; Xiong, Jing; Hu, Yue; Pan, Liteng; Liao, Zhengqiao; Zhang, Xuemei; Guo, Wei; Wu, Fengkai; Xu, Jie; Hu, Erliang; Lan, Hai; Lu, Yanli
ABSTRACT: It has long been considered that mechanical impedance on root will restrict root elongation and consequently promote radial growth. When seedlings grew in sands, we did observe radial expansion of roots and it, however, arose before elongation restriction. Mechanical impedance of sands can be classified into frontal- and lateral-type based on the interaction site of root. Therefore, we suspected that radial expansion might be mainly stimulated by lateral- rather than frontal-impedance. To verify our speculation, roots were exposed to frontal- and lateral-impedance separately. Small plastic caps were used to provide pure frontal impedance on root tips and cylindrical plastic containers were used to provide pure lateral impedance. Root elongation was remarkably suppressed under the frontal impedance of plastic caps, and more than that in sand-condition. However, the radial expansion of the plastic-cap-fitted roots was far inferior to that of the sand-cultured roots. Microstructural analysis revealed that sand-condition thickened root largely dependents on cortical expansion, whereas plastic cap did it mainly by thickening stele. In cylindrical plastic containers, mechanical impedance came only from the lateral direction and promoted the expansion of cortex like sand-condition. Thus, we proposed that the expansion of cortex and the consequent radial growth of roots were mainly due to lateral impedance when seedlings grew in sands.